(untitled) (American Journal of Pedagogical and Educational Research, 2024)
The article examines the implementation of mental activity in the course of empirical cognition, collecting information about an object and making preliminary generalizations, creating a general description of an object, collecting data based on observations, systematizing and classifying data.